2019
DOI: 10.26555/humanitas.v16i2.10981
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being among mothers of children with autism spectrum disorder: The role of family function

Abstract: The mother of children with autism is the most vulnerable person to have stress and depression. Therefore they need positive psychological well-being to optimize the caring of children. Family is the primary environment in supporting the mother's mental health. This study aimed to find out how family functions correlate with psychological well-being among the mother of a child with autism. A quantitative approach was applied, involving 142 mothers who had autistic children selected through purposive sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…mothers can be rude which reflects low compassionate love in parenting [40]. Furthermore, the low compassionate love of mothers in parenting can form low psychological well-being in mothers and children [26]. Then the mother's need for social support from the closest person, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mothers can be rude which reflects low compassionate love in parenting [40]. Furthermore, the low compassionate love of mothers in parenting can form low psychological well-being in mothers and children [26]. Then the mother's need for social support from the closest person, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One of the components of family environment is social support perceived by individuals. An initial research suggested that supports from family consisting of spouse, siblings, and extended family in parenting children with ASD increases mother wellbeing in Indonesia [26]. Husband's social support can increase endurance and psychological wellbeing of their wives as mothers of children with ASD [27] [28].…”
Section: Introductionmentioning
confidence: 99%
“…37,41 Achieving a high level of family functioning will lead to higher family well-being which refers to the degree to which a family is adjusted in terms of concerns about health, tension, cheerfulness, anger, fear, sadness, and general concerns. 42 Ultimately, the family will be able to provide the best care for chronically ill children resulting in a better quality of life for the children. This is congruent with a study by Yang et al, 43 which found that there was a significant relationship between family functioning and health-related quality of life in chronically ill children.…”
Section: Consequencesmentioning
confidence: 99%
“…Previous research has shown that family support contributes to the psychological well-being of mothers. Desiningrum et al (2019) found that family support contributes to individual psychological well-being because the individual feels the family loves and accepts him as he is and can understand the shortcomings and strengths of his potential. Such social support might become a significant factor in developing mothers' psychological well-being (Gorlin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%